2019
DOI: 10.1186/s12885-019-5540-5
|View full text |Cite
|
Sign up to set email alerts
|

Peptide receptor radionuclide therapy in patients with medullary thyroid carcinoma: predictors and pitfalls

Abstract: Background For progressive metastatic medullary thyroid carcinoma (MTC), the available treatment options with tyrosine kinase inhibitors result in grade 3–4 adverse events in a large number of patients. Peptide Receptor Radionuclide Therapy (PRRT), which has also been suggested to be a useful treatment for MTC, is usually well tolerated, but evidence on its effectivity is very limited. Methods Retrospective evaluation of treatment effects of PRRT in a highly selected gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 37 publications
4
46
0
3
Order By: Relevance
“…However, none of these treatments were able to promote complete remission and cure of the disease and had some important and serious side effects such as ECG alterations, diarrhea and hypertension. 34,35 We found median a PFS of 24 months (95% CI: 15.1-32.9 months) after first 177 Lu-DOTATATE PRRT, which was between cabozantinib group (PFS-11.2 months) and vandetanib group (PFS-30.5 months) reported in the literature; also PRRT welltolerated with fewer side effects of low grade severity was demonstrated in our study. However, retrospective nature of our study was major limitation.…”
Section: Discussionsupporting
confidence: 73%
“…However, none of these treatments were able to promote complete remission and cure of the disease and had some important and serious side effects such as ECG alterations, diarrhea and hypertension. 34,35 We found median a PFS of 24 months (95% CI: 15.1-32.9 months) after first 177 Lu-DOTATATE PRRT, which was between cabozantinib group (PFS-11.2 months) and vandetanib group (PFS-30.5 months) reported in the literature; also PRRT welltolerated with fewer side effects of low grade severity was demonstrated in our study. However, retrospective nature of our study was major limitation.…”
Section: Discussionsupporting
confidence: 73%
“…Therefore, alternative treatment options with fewer side effects were needed. With the detection of SSTR expression in MTC, PPRT has become the new treatment option (9). According to previous studies, the response rates were 29-80%, in our study we found stable disease response in all 3 patients who underwent treatment response evaluation (18,24).…”
Section: Discussionsupporting
confidence: 68%
“…There were small pilot studies performed in Europe that documented the utility of treatment of progressive RAI-non-avid metastatic DTC and MTC with SSTR agonists radiolabeled with 177 Lutetium or 86 Ytrium. The overall response rate was similar to current standard-of-care therapy with TKIs, while the quality of life was better and complication rate was lower after the therapy with PRRT (Table 2) [111][112][113][130][131][132].…”
Section: Peptide Receptor Radionuclide Therapy In Thyroid Cancermentioning
confidence: 79%